Dokazi za pristope in metode delovne terapije v poklicni rehabilitaciji oseb s pridobljeno možgansko poškodbo - Švajger, Andreja (Rehabilitacija (Ljubljana), 2012)
Background: In vocational rehabilitation, occupational therapists are daily faced with the challenges of deciding on methods of working with persons with acquired brain injury (ABI). To make these decisions, they need evidence about the effectiveness of different approaches and methods. Methods: We conducted a systematic literature review. The selection of literature was based on weighing best evidence from different types of studies, accessed mostly over electronic data bases (Medline, PEDro, OTseeker and MOHO Evidence Brief). The review process followed the Cochrane Handbook of Systematic Review. Studies were classified according to the American Association of Occupational Therapists' levels of evidence. Results: The strongest evidence confirms the effectiveness of cognitive rehabilitation of persons after ABI using the approach of teaching compensatory strategies and external devices. Strong evidence also exists for the client and occupation based approach. Studies on assessment approaches and methods support the use of assessments on all levels and in all areas of functioning, including barriers and opportunities in the environment. The strongest support can be found for the combination of standardised tests of memory, perception and apraxia with the assessment of the quality of occupational performance. Studies about approaches and methods of interventions support the efficiency of compensatory strategies and external aids for learning functional tasks and overcoming executive functions deficits. Conclusions: Literature review directs occupational therapists working in vocational rehabilitation of persons after ABI towards assessing person's functioning by combining approaches and methods on different levels and in relation to the characteristics and demands of the work environment. Successful inclusion into work is more likely when the intervention is work-place based and client-centred.
Keywords: Brain Injuries; delovna terapija; možganske poškodbe; Occupational Therapy; occupational therapy assessment and intervention; poklicna rehabilitacija; rehabilitacija; Rehabilitation, Vocational; vocational rehabilitation; work integration